2020
DOI: 10.1093/carcin/bgaa090
|View full text |Cite
|
Sign up to set email alerts
|

Andrographis-mediated chemosensitization through activation of ferroptosis and suppression of β-catenin/Wnt-signaling pathways in colorectal cancer

Abstract: Colorectal cancer (CRC) remains one of the leading causes of cancer-related mortality in the United States. As much as 50-60% of CRC patients develop resistance to 5-fluorouracil (5FU)-based chemotherapeutic regimens, attributing the increased overall morbidity and mortality. In view of the growing evidence that active principles in various naturally-occurring botanicals can facilitate chemosensitization in cancer cells, herein, we undertook a comprehensive effort in interrogating the activity of one such bota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
51
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 55 publications
2
51
0
1
Order By: Relevance
“…The inhibition of GCLM will induce the ferroptosis. The gene expression profiles show the GCLM level is up-regulated in many tumors [ 33 , 34 ]. Moreover, the GCLM expression level is negatively associated with patients’ relapse-free survival (RFS) and OS [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The inhibition of GCLM will induce the ferroptosis. The gene expression profiles show the GCLM level is up-regulated in many tumors [ 33 , 34 ]. Moreover, the GCLM expression level is negatively associated with patients’ relapse-free survival (RFS) and OS [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The existence of GLCM that drives ferroptosis has important implications for cancer therapy. A recent study by Sharma P identified the Andrographis, a medicine herb, could overcome the colorectal cancer chemoresistance by regulating the ferroptosis genes, such as GCLM [ 34 ]. Therefore, drugs that target ferroptosis can be exploited and provide an efficient strategy for clinical application.…”
Section: Discussionmentioning
confidence: 99%
“…Aspirin dosing in our CD1 Nude mouse model [ 36 , 37 ], which mimicked low-dose aspirin use in humans, based on profound platelet COX-1 inhibition but an absence of systemic COX-2 inhibition, did not increase the sensitivity of MC38 mouse CRC cell tumours to EPA in vivo, in direct contrast to the corresponding in vitro data. We demonstrated that there was inefficient inhibition of PGE 2 production in CRC cell tumour tissue, despite efficient systemic COX-1 inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…The inhibition of GCLM will induce the ferroptosis. The gene expression pro les show the GCLM level is up-regulated in many tumors [33][34] . Moreover, the GCLM expression level is negatively associated with patients' relapse free survival (RFS) and OS [33] .…”
Section: Discussionmentioning
confidence: 99%
“…The existence of GLCM that drives ferroptosis has important implications for cancer therapy. A recent study by Sharma P identi ed the Andrographis, a medicine herb, could overcome the colorectal cancer chemoresistance by regulating the ferroptosis genes, such as GCLM [34] . Therefore, drugs that target ferroptosis can be exploited and provide an e cient strategy for clinical application.…”
Section: Discussionmentioning
confidence: 99%